Albania : Staff Report for the 2013 Article IV Consultation and Request for Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This 2013 Article IV Consultation for Albania focuses on economic developments and policies that have led to weakening and imbalance of the economy. It highlights that high nonperforming loans (NPLs) are constraining credit growth, and weak external drivers are preventing a sustained reduction in external imbalances. Reduction in NPLs would safeguard financial stability and help release credit supply constraints by lowering bank risk aversion. The authorities have requested a three-year arrangement with proposed access equivalent to SDR 295.42 million.